Rhinitis radiofrequency ablation: FEM analysis and experiments - Song, Yuqi (Kansas State University, 2018)
The primary objective of this research is to implement an experimentally validated computational model to guide device design and selection of energy delivery strategies for treating chronic rhinitis by radiofrequency ablation. Chronic rhinitis is one of the most common global health problems. It is not life-threatening but has a severe impact on quality of life. Direct cost by chronic rhinitis is enormous and places a burden on societies. Radiofrequency ablation is proposed to be as an efficient treatment providing symptom relief and avoiding side effects compared to traditional therapies. Three-dimensional finite element method (FEM) models were developed to investigate RFA devices and energy delivery strategies. FEM computational models could provide vital variable profiles that are technically challenging to determine through experiments. Also, computer simulation could reduce the number of experimental procedures during the device design process. First, single pair bipolar RF ablation experiments were performed to validate FEM simulations using the same geometry as in experiments. The data from experiments and simulations had a high correlation (R = 0.91). Second, the Neurent basket electrode was employed in experimental ablations in egg white, for comparison against FEM simulations. Smaller lesion sizes were observed in experiments compared to simulations, attributed to thermal convection that was not accounted for in simulation. Finally, FEM simulations were used to investigate the effects of basket electrode diameter, length, and applied power on ablation zone formation. A shorter but wider electrode with a maximum spacing distance between two pairs of electrodes is preferable to create discontiguous ablation zones. 50% duty cycle was recommended to create thermal ablation zones with gradually increasing temperature and sufficiently large thermal lesion volumes.
Keywords: radiofrequency ablation; rhinitis; thermal ablation; medical devices